2006
DOI: 10.1158/1535-7163.mct-06-0273
|View full text |Cite
|
Sign up to set email alerts
|

Cantharidin-induced mitotic arrest is associated with the formation of aberrant mitotic spindles and lagging chromosomes resulting, in part, from the suppression of PP2Aα

Abstract: Cantharidin, a natural vesicant, inhibits the activity of several PPP family phosphatases, displays antitumor activity, and induces apoptosis in many types of tumor cells. However, the molecular mechanisms underlying the antitumor activity of cantharidin are not clear. Here, doseresponse studies confirm a strong correlation between the suppression of phosphatase activity and cell death. Flow cytometry analysis indicates that before apoptosis, cantharidin delays cell cycle progression following DNA replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 33 publications
3
49
0
Order By: Relevance
“…Small molecules derived from cantharidin (a vesicant originally extracted from beetles) or its demethylated homolog (norcantharidin) mimic the effects of okadaic acid (16,17). Modest clinical benefit of cantharidin is constrained by urologic toxicity, and norcantharidin, although less toxic, has limited effectiveness (17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small molecules derived from cantharidin (a vesicant originally extracted from beetles) or its demethylated homolog (norcantharidin) mimic the effects of okadaic acid (16,17). Modest clinical benefit of cantharidin is constrained by urologic toxicity, and norcantharidin, although less toxic, has limited effectiveness (17).…”
Section: Resultsmentioning
confidence: 99%
“…Small molecules derived from cantharidin (a vesicant originally extracted from beetles) or its demethylated homolog (norcantharidin) mimic the effects of okadaic acid (16,17). Modest clinical benefit of cantharidin is constrained by urologic toxicity, and norcantharidin, although less toxic, has limited effectiveness (17). We synthesized a series of norcantharidin derivatives and characterized their antiphosphatase and anticancer activity in vitro (18) and selected LB1.2 for more detailed study in vivo alone and in combination with TMZ, the standard drug for the palliative treatment of GBM.…”
Section: Resultsmentioning
confidence: 99%
“…[59][60][61] Inhibition of PP2A with either of these compounds results in abnormal mitotic figures characteristic of mitotic catastrophe, a form of cell death distinct from apoptosis. [62][63][64] To overcome the toxicities of okadaic acid and cantharidins, a competitive small molecule inhibitor of PP2A called LB100 (Lixte Biotechnology, East Setauket, NY) was recently developed and was studied in a variety of pre-clinical cancer models. These pre-clinical studies demonstrated that LB100 exhibits potent chemo-and radio-sensitizing properties, which has prompted interest in evaluation of LB100 in human clinical trials.…”
Section: Pp2a As An Oncogenementioning
confidence: 99%
“…7 Moreover, CTD has been shown to increase the level of Bax, inhibit the expression of B-cell lymphoma 2 and survivin, 8 and regulate the production of reactive oxygen species, subsequently inducing apoptotic cell death. 9 However, the toxicity of CTD, including the damage to mammals' urinary system, hematemesis, dysuria, liver congestion, and the risk of aborticide, remains a great challenge for its further development in clinical applications. 1 Therefore, scientists have persisted in the search to maximize its potential, and many CTD derivatives and several novel drug-delivery systems have been developed.…”
Section: Introductionmentioning
confidence: 99%